Harmonic Analysis and Performance of a VFD-Controlled Single-Phase Motor - Jakariya, Jakariya; Doane Puri Mustika (Politeknik Negeri Batam, 2025)
The application of Variable Frequency Drives (VFDs) in single-phase induction motors is increasingly common, although it may introduce harmonic distortion that affects power quality. This study analyzes harmonic characteristics and motor performance under variable frequency operation. Measurements of voltage and current harmonics were carried out using a Fluke 434 Power Quality Analyzer at VFD frequencies ranging from 10 to 50 Hz. The results indicate that voltage harmonic distortion (THD-V) decreased from 5,0% to 3,2% on L1 and from 5,8% to 4,1% on the neutral conductor, remaining within IEEE 519-2014 limits. In contrast, current distortion (TDD) reached 71,8% at 50 Hz but decreased to 23% at 20 Hz due to network impedance effects. Dominant harmonics were observed at H3–H13, with triplen harmonics prevailing in the neutral line. Overall, VFD-based frequency control improves motor efficiency and voltage quality but requires additional filtering to limit current distortion within standards.